A novel ternary combination of deep eutectic solvent-alcohol (DES-OL) system for synergistic and efficient delignification of biomass. (October 2018) - Kandanelli, Ramesh; Thulluri, Chiranjeevi; Mangala, Ramkumar; Rao, Peddy V.C.; Gandham, Sriganesh; Velankar, Harshad R.
Graphical abstract: A novel ternary system based on a combination of deep eutectic solvent and an alcohol was used for effective pretreatment of lignocellulosic biomass and lignin fractionation. Highlights: A novel green ternary solvent system for delignification of lignocellulosic biomass. Pretreatment was performed for three different biomass materials. About 50% of lignin removal was achieved under mild treatment conditions. Structural changes and lignin recovery were validated by microscopy (Optical & FE-SEM) and CPMAS NMR, respectively. Abstract: A novel ternary system consisting of deep eutectic solvent-alcohol (DES-OL) mixture was developed for the effective delignification of lignocellulosic biomass. Optimization studies included selecting suitable co-solvent (among n -BuOH, n -PrOH & EtOAc) for treating biomass (rice husk, rice straw and wheat straw), altering the DES-to-alcohol ratio (2:1, 1:1 and 1:2) as well as the reaction temperature (50, 80 and 120 °C). The highest delignification (∼50%) was observed using n -butanol assisted DES (ChCl: OA) at a ratio of 2:1, with high solid loading of 15% ( w/v ) at 120 °C (∼1.2 bar) in a 60 min reaction. Post pretreatment, high purity lignin was recovered after distilling off butanol for recycling. Microscopy and CPMAS/NMR studies confirmed the effectiveness of DES-OL pretreatment on biomass delignification.